Harmonization and qualification of intracellular cytokine staining to measure influenza-specific CD4+ T cell immunity within the FLUCOP consortium - Begue, Sarah; Waerlop, Gwenn; Salaun, Bruno; Janssens, Michel; Bellamy, Duncan; Cox, Rebecca Jane; Davies, Richard; Gianchecchi, Elena; Medaglini, Donata; Montomoli, Emanuele; Pettini, Elena; Leroux-Roels, Geert; et al. (Frontiers in Immunology, 2022)
Despite the knowledge that cell-mediated immunity (CMI) contributes to the reduction of severe influenza infection, transmission, and disease outcome, the correlates of protection for cell-mediated immunity remain still unclear. Therefore, measuring the magnitude and quality of influenza-specific T cell responses in a harmonized way is of utmost importance to improve characterisation of vaccine-induced immunity across different clinical trials. The present study, conducted as part of the FLUCOP project, describes the development of a consensus protocol for the intracellular cytokine staining (ICS) assay, in order to reduce inter-laboratory variability, and its qualification. In order to develop a consensus protocol, the study was divided into different stages. Firstly, two pilot studies evaluated critical parameters in the analytical (read-outs) and post-analytical (gating strategies and data analysis) methods applied by eight different laboratories within the FLUCOP consortium. The methods were then harmonized by fixing the critical parameters and the subsequent consensus protocol was then qualified by one FLUCOP member. The antigen-specific cell population was defined as polypositive CD4+ T cells (i.e. positive for at least two markers among CD40L/IFNγ/IL2/TNFα), which was shown to be the most sensitive and specific read-out. The qualification of this consensus protocol showed that the quantification of polypositive CD4+ T cells was precise, linear and accurate, and sensitive with a lower limit of quantification of 0.0335% antigen-specific polypositive CD4+ T cells. In conclusion, we provide the description of a harmonized ICS assay, which permits quantitative and qualitative evaluation of influenza vaccine-induced T cell responses. Application of this harmonized assay may allow for future comparisons of T cell responses to different influenza vaccines. It may facilitate future assessments of potential correlates of protection with the promise of application across other pathogens.